Analisis Perubahan Pendekatan Mahkamah Konstitusi terhadap Ambang Batas Presiden - Ummu Hanie; Sidik Adi Purnama; Faiz Rahmanto (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
The Presidential Threshold is a constitutional issue that continues to spark debate in Indonesia’s democratic system, as it is viewed as undermining electoral justice and limiting citizens’ choices in presidential elections. The Constitutional Court (MK) has repeatedly received petitions for judicial review of Article 222 of Law Number 7 of 2017 on General Elections. This study aims to analyze the Court’s shifting stance in reviewing the constitutionality of the Presidential Threshold and to identify the legal reasoning underlying its decisions. Employing a normative juridical approach combined with comparative analysis of Constitutional Court rulings from 2008 to 2024, the study finds that various arguments claim Article 222 contradicts citizens’ political rights, the principle of popular sovereignty, and substantive justice. The findings highlight evolving dynamics in the Court’s jurisprudence and the ongoing challenge of maintaining consistency in constitutional interpretation amid political pressures and broader social change.